2016
DOI: 10.1016/j.rbre.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis and systemic lupus erythematosus

Abstract: A large number of studies have shown a potential association between periodontal and autoimmune diseases, such as rheumatoid arthritis and systemic lupus erythematosus (SLE). Similar mechanisms of tissue destruction concerning periodontitis and other autoimmune diseases have stimulated the study of a possible relationship between these conditions. This study aims to review the literature about this potential association and their different pathogenic mechanisms. Considering that periodontal disease is a diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 45 publications
0
24
0
4
Order By: Relevance
“…This fact suggests that the persistence of a chronic inflammatory process related to JDM disease could be responsible for the greater periodontal involvement and reinforces that periodontitis is a progressive phenomenon, beginning with gingivitis, followed by the destruction of the periodontal ligaments and bone reabsorption and ending in dental attachment loss [4]. In fact, although initial aspects of periodontitis, such as increased PCS and PCI, were associated with patients with JDM and dyslipidemia, none of the patients studied was classified as having periodontitis (PCI > 3 mm), which is rarely observed in pediatric age group [15]. Future prospective studies should be necessary to clarify this point.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…This fact suggests that the persistence of a chronic inflammatory process related to JDM disease could be responsible for the greater periodontal involvement and reinforces that periodontitis is a progressive phenomenon, beginning with gingivitis, followed by the destruction of the periodontal ligaments and bone reabsorption and ending in dental attachment loss [4]. In fact, although initial aspects of periodontitis, such as increased PCS and PCI, were associated with patients with JDM and dyslipidemia, none of the patients studied was classified as having periodontitis (PCI > 3 mm), which is rarely observed in pediatric age group [15]. Future prospective studies should be necessary to clarify this point.…”
Section: Discussionmentioning
confidence: 69%
“…Periodontitis is a progressive phenomenon, beginning with gingivitis, followed by the destruction of the periodontal ligaments and bone reabsorption and ending in dental attachment loss [4]. Gengivitis and/or periodontitis have been seldom studied in pediatric autoimmune diseases, like juvenile idiopathic arthritis and juvenile systemic lupus erythematosus [10][11][12][13][14][15] Recently the association between periodontal disease and dyslipidemia was reported in healthy adults [16].…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils and phagocytes play an important role in eliminating fungi. 10 Sete, et al 1 state that, with regard to SLE, there are several possible causes such as: disruption of T cell function, genetic defects in the immune response control system, abnormal macrophage functioning, B cell damage, ineffective host response to an infectious agent or a combination of several of these elements.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Approximately 75% of people with SLE present various symptoms in the oral cavity including an oral ulcer located in the buccal mucosa, palate, periodontitis with floating teeth and a dry mouth accompanied by a burning sensation, especially when eating spicy or hot foods. [1][2][3]5 According to Sete, et al 1 several studies exist confirming the association between chronic periodontitis and SLE conditions, characterized by damaged periodontal tissue resulting in floating teeth and ulcers on the oral mucosa, and most of them on the hard palate.…”
mentioning
confidence: 99%
“…The immunological pathway of SLE resembles the one that develops during periodontitis and peri-implantitis 42 . Therefore, it is possible that SLE aggravates the periodontal and peri-implants diseases and may result in a higher possibility of implant loss compared to healthy people 43 . Only one study referring to implant placement in patient suffering from SLE was found.…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%